Investments in timberland: investors\' strategies and economic perspective in Brazil - Silva, Bruno Kanieski da (2013)
Forest plantations provide essential services for human beings. More recently, population and economic growth has increasingly intensified the demand for forest products. Forest activities are expanding to new areas due to low land prices and governmental incentives in Brazil. Among others; Timberland Investment Management Organizations (TIMOs) are the type of invertors that have significantly increased their participation in the timberland market. The purpose of this thesis is to investigate investor\'s strategies and the mains aspects related to forest investments in Brazil. The thesis is divided into two chapters. The first chapter investigates the strategies used by TIMOs in Brazil and their declared expectations on returns. The second chapter offers a comprehensive analysis of the level and variability of the return rate for three different regions in Brazil.